Effects of lasmiditan on simulated driving performance: Results of two randomized, blinded, crossover studies with placebo and active controls. (25th May 2020) - Pearlman, Eric M.; Wilbraham, Darren; Dennehy, Ellen B.; Berg, Paul H.; Tsai, Max; Doty, Erin G.; Kay, Gary G.
Abstract: Objective: To evaluate the impact of lasmiditan, an oral, centrally‐penetrant, selective serotonin 1F (5‐HT1F ) receptor agonist developed for the acute treatment of migraine, on simulated driving. Methods: Healthy adult volunteers enrolled in two randomized, placebo and active comparator‐controlled, crossover studies. Study 1 ( N = 90) tested lasmiditan (50‐, 100‐, 200‐mg), alprazolam (1‐mg), and placebo at 1.5 hr post‐dose. Study 2 ( N = 68) tested lasmiditan (100‐, 200‐mg), diphenhydramine (50‐mg, administered 2 hr pre‐assessments), and placebo at 8, 12 and 24 hr post‐dose. Driving performance was assessed using a validated driving simulator employing a 100 km driving scenario. Standard deviation of lateral position (SDLP), a measure of lane position control, was the primary endpoint. Results: Assay sensitivity was confirmed by increased SDLP for active comparators at 1.5‐ and 8‐hr time points. Lasmiditan doses showed significant driving impairment versus placebo at 1.5 hr post‐dose. Lasmiditan doses were non‐inferior to placebo at 8 hr. Driving impairment was concentration‐dependent at 1.5 hr but not at 8 hr. Common adverse events were central nervous system‐related and mild‐to‐moderate in severity. Conclusions: Lasmiditan was associated with impaired simulated driving performance at 1.5 hr post‐dose, but showed no clinically meaningful impairment at 8 hr post‐dose.